The Use of Al-Maslahah Al-Mursalah in The Ijtihad of Imam Ash-Shafi’i - Muhammad Hidayat (Tabayyanu : Journal Of Islamic Law, 2025)
The position of Imam al-Shafi'i regarding al-maslahah al-mursalah remains one of the most debated issues in Islamic legal theory. While the dominant view maintains that he rejected al-maslahah al-mursalah as an independent legal source, other scholars argue that he implicitly applied it through his legal reasoning. Existing studies primarily focus on determining whether Imam al-Shafi'i accepted or rejected al-maslahah al-mursalah, but they have not sufficiently explained the epistemological relationship between qiyas and al-maslahah al-mursalah within his legal methodology. This study aims to reconstruct that relationship by examining Imam al-Shafi'i's theory of qiyas and its application in selected fiqh cases. Employing normative legal research with conceptual, historical, and usul al-fiqh approaches, this study analyzes classical legal sources and relevant contemporary scholarship through qualitative and interpretative methods. The findings demonstrate that Imam al-Shafi'i rejected al-maslahah al-mursalah only as an autonomous legal proof (dalil mustaqill), while substantively integrating considerations of public welfare into the methodological structure of qiyas through the identification of 'illah and al-ma'na. Accordingly, maslahah functions not as an independent source of law but as the internal normative logic guiding analogical reasoning toward the realization of justice and the objectives of the Sharia (maqasid al-shari'ah). The novelty of this study lies in reconstructing Imam al-Shafi'i's legal methodology into an integrated epistemological model linking revelation, 'illah, al-ma'na, qiyas, and maslahah. This reconstruction contributes to contemporary usul al-fiqh scholarship by providing a more coherent framework for understanding Shafi'i legal reasoning and its relevance to addressing modern legal issues while maintaining fidelity to revealed sources.